A survey of the density, distribution, and Schistosoma japonicum infection of Oncomelania quadrasi collected from Brgy. San Agustin, Brgy. San Isidro, and Brgy. Campetic in Palo, Leyte - Getalado, Rosalind Santa P. (2016)
Schistosoma japonicum is the causative agent of the prevalent Schistosomiasis in the Philippines. This parasite is transmitted from its intermediate host, Oncomelania quadrasi, to its definitive mammalian host. In this study, the presence of S. japonicum in the O. quadrasi collected from the study site was determined. The primary objective of this study was to determine the density and Schistosoma infection of snails from all sampling sites. Three barangays in Palo, Leyte were chosen as study sites: San Isidro, San Agustin, and Campetic. In each barangay, 3 collecting stations were selected. Intensive snail search and random ring sampling were done. Collected snails were processed in the laboratory for the detection of the presence of S. japonicum. The snail densities varied across study sites. Snail density was highest in Brgy. San Isidro and Brgy. San Agustin and zero in Brgy. Campetic. Environmental factors and proximity of human habitations to snail habitats were believed to influence these differences in snail densities.